Exploration of the Synergistic Regulation Mechanism in Cerebral Ganglion and Heart of Eriocheir sinensis on Energy Metabolism and Antioxidant Homeostasis Maintenance under Alkalinity Stress - Meiyao Wang; Jun Zhou; Gangchun Xu; Yongkai Tang (MDPI AG, 2024)
(1) The development and utilization of the vast saline-alkali land worldwide is an important way to solve the worsening food crisis. Eriocheir sinensis, due to its strong osmotic regulation capability and its characteristics of being suitable for culturing in alkaline water, has become a potential aquaculture species in saline-alkali water. The brain and heart are the key tissues for signal transduction and energy supply under environmental stress. (2) This study is the first to explore the synergistic regulatory molecular mechanism by integrated analysis on cerebral ganglion proteomics and heart metabolomics of Eriocheir sinensis under alkalinity stress. (3) The results indicate that the cerebral ganglion and heart of E. sinensis were closely related in response to acute alkalinity stress. The differential regulatory pathways mainly involved regulation of energy metabolism, amino acid metabolism, and homeostasis maintenance. Importantly, alkalinity stress induced the regulation of antioxidants and further adjusted longevity and rhythm in the cerebral ganglion and heart, reflecting that the cerebral ganglion and heart may be the key tissues for the survival of Eriocheir sinensis under an alkalinity environment. (4) This study provides a theoretical reference for research on the regulation mechanism of E. sinensis under alkalinity condition and contributes to the development of aquaculture in saline-alkali water.